2003
DOI: 10.1063/1.1573632
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations of mode selective tunneling dynamics in CH312OH and CH313OH

Abstract: A simplified formulation of the harmonic reaction path Hamiltonian (RPH) approach is used to calculate mode specific tunneling splittings and stereomutation times in CH312OH and CH313OH. The experimental torsional spectrum is very well reproduced, as well as the few known isotope shifts. The mode specific changes in tunneling splitting are investigated for the excitation of fundamentals and OH stretching overtones. Good agreement between experiment and the RPH model is obtained, except for excitations of modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 63 publications
4
66
0
Order By: Relevance
“…This mode corresponds to the torsional motion of the OH fragment which is expected to be very floppy, and so large amplitude motion should be taken into account to reproduce the fundamental of 12 accurately. 52 Second, the calculated 3 gives a large error of 6.1% in the direct cc-VSCF method, which suggests that perhaps a higher level of electronic structure theory should be used or perhaps high levels of correlation in the vibrational state calculations. Finally, 1 calculated by the cc-VSCF/2MR-QFF method gives a large deviation from the corresponding direct cc-VSCF result of ͒ of methanol obtained from the harmonic approximation, cc-VSCF/2MR-QFF, and the direct cc-VSCF ͑2MR͒ calculations, at the level of MP2/cc-pVTZ.…”
mentioning
confidence: 99%
“…This mode corresponds to the torsional motion of the OH fragment which is expected to be very floppy, and so large amplitude motion should be taken into account to reproduce the fundamental of 12 accurately. 52 Second, the calculated 3 gives a large error of 6.1% in the direct cc-VSCF method, which suggests that perhaps a higher level of electronic structure theory should be used or perhaps high levels of correlation in the vibrational state calculations. Finally, 1 calculated by the cc-VSCF/2MR-QFF method gives a large deviation from the corresponding direct cc-VSCF result of ͒ of methanol obtained from the harmonic approximation, cc-VSCF/2MR-QFF, and the direct cc-VSCF ͑2MR͒ calculations, at the level of MP2/cc-pVTZ.…”
mentioning
confidence: 99%
“…Fehrensen et al 7 applied an adiabatic reaction path Hamiltonian to account for both the decrease of the torsional tunneling splittings with OH stretch (ν 1 ) excitation and also the inverted torsional tunneling splittings in the first excited states of the asymmetric CH stretches, ν 2 and ν 9 . They found that a geometric phase of -1 was accumulated for the CH vibrations ν 2 and ν 9 on a torsional rotation of 2π .…”
mentioning
confidence: 99%
“…The adiabatic approximation has been applied to methanol, [6][7][8] the high frequency vibrations being the OH and CH stretches (3860, 2999, 2956, and 2844 cm −1 ) and the low frequency coordinate being the torsional angle, γ . Fehrensen et al 7 applied an adiabatic reaction path Hamiltonian to account for both the decrease of the torsional tunneling splittings with OH stretch (ν 1 ) excitation and also the inverted torsional tunneling splittings in the first excited states of the asymmetric CH stretches, ν 2 and ν 9 .…”
mentioning
confidence: 99%
“…The accuracy of the RPH approach itself was discussed in detail previously [25,43]. We have also shown recently that with appropriate empirical corrections the modest intrinsic ab initio error in the electronic structure calculations can be further reduced [63]. Fig.…”
Section: Hoclh + Dclod + and Tclot +mentioning
confidence: 95%